Acacia sieberana Dc., a Promising Exotic for Tropical Semi-arid Zones of India - Hingorani, C. R.; Pant, H. C. (Indian Forester, 1971)
The arid and semi-arid regions of India are characterised by extremes of tempetature, low rainfall, Severe drought, high wind velocity and scanty vegetation of thorny scrub type. Acacia sieberana DC., an economically important exotic from the Sudan holds promise of being introduced as a successful species for topical semi-arid to low rainfall areas. The information is based on limited trials conducted at the Forest Research Institute and Colleges (New Forest), Dehra Dun and Central Arid Zone Research Institute, Jodhpur.